Evolution of the dipole polarizability in the stable tin isotope chain - S. Bassauer; P. von Neumann-Cosel; P.-G. Reinhard; A. Tamii; S. Adachi; C.A. Bertulani; P.Y. Chan; G. Colò; A. D'Alessio; H. Fujioka; H. Fujita; Y. Fujita; et al. (Physics Letters B, 2020)
The dipole polarizability of stable even-mass tin isotopes 112,114,116,118,120,124Sn was extracted from inelastic proton scattering experiments at 295MeV under very forward angles performed at RCNP. Predictions from energy density functionals cannot account for the present data and the polarizability of 208Pb simultaneously. The evolution of the polarizabilities in neighboring isotopes indicates a kink at 120Sn while all model results show a nearly linear increase with mass number after inclusion of pairing corrections.